PROCALCITONIN TESTING IN RHEUMATOLOGY - D. V. Bukhanova; B. S. Belov; G. M. Tarasova; A. G. Dilbaryan (Klinicist, 2017)
Currently, differential diagnosis of systemic bacterial infection and active rheumatic process remains a challenging problem in rheumatology. In the review, current data on the role of procalcitonin biomarker in diagnosis and differential diagnosis of rheumatic diseases (RD) and infectious pathology are presented. In particular, some authors recommend procalcitonin (PCT) test as a marker of bacterial infection in bones and joints at levels above 0.5 ng/ml; at PCT level below 0.3 ng/ml, infection can be ruled out. In patients with microcrystalline arthritis, data on the significance of PCT for differential diagnosis are contradictory. PCT level doesn’t correlate with systemic lupus erythematosus activity and is elevated only during bacterial infection proportionally to its systematicity. In some studies, elevated PCT level was observed in ANCA-associated vasculitis with high activity without bacterial infection. It was shown that in 80 % of adults with Still’s disease, PCT level was higher than the threshold value even without infection. For patients with RD hospitalized in intensive care units, PCT clearance is a more informative predictive characteristic than its level, regardless of the cause of PCT elevation (infection, injury, severe organ damage, etc.); slowdown of its decrease is a factor of poor prognosis and is associated with higher mortality. At the same time, PCT level positively correlates with the SOFA score in presence of bacterial infection. For some rheumatic diseases, the threshold PCT value at which the test has optimal sensitivity and specificity is yet to be established. Nonetheless, PCT should be evaluated in relation to the clinical picture and data of additional examinations. The effect of various therapy methods used in rheumatology on PCT level requires further research.